2016
DOI: 10.1371/journal.pone.0158489
|View full text |Cite
|
Sign up to set email alerts
|

Performance of the Finnish Diabetes Risk Score and a Simplified Finnish Diabetes Risk Score in a Community-Based, Cross-Sectional Programme for Screening of Undiagnosed Type 2 Diabetes Mellitus and Dysglycaemia in Madrid, Spain: The SPREDIA-2 Study

Abstract: AimTo evaluate the performance of the Finnish Diabetes Risk Score (FINDRISC) and a simplified FINDRISC score (MADRISC) in screening for undiagnosed type 2 diabetes mellitus (UT2DM) and dysglycaemia.MethodsA population-based, cross-sectional, descriptive study was carried out with participants with UT2DM, ranged between 45–74 years and lived in two districts in the north of metropolitan Madrid (Spain). The FINDRISC and MADRISC scores were evaluated using the area under the receiver operating characteristic curv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
46
0
11

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(62 citation statements)
references
References 37 publications
5
46
0
11
Order By: Relevance
“…Similar findings were also put forward by studies from the US and the UK [12,23]. Interestingly, a study from Spain found a high proportion of undiagnosed diabetes in females by HBA1c criteria and/or OGTT criteria [24], which was in agreement with our results. Altogether, these studies suggest that the distribution of diabetes by sex may be undergoing a steady shift.…”
Section: Discussionsupporting
confidence: 93%
“…Similar findings were also put forward by studies from the US and the UK [12,23]. Interestingly, a study from Spain found a high proportion of undiagnosed diabetes in females by HBA1c criteria and/or OGTT criteria [24], which was in agreement with our results. Altogether, these studies suggest that the distribution of diabetes by sex may be undergoing a steady shift.…”
Section: Discussionsupporting
confidence: 93%
“…Because gender is not collected as a separate question, but can be collected from the question on waist circumference, where a separate set of values is available for men and women, FINDRISC questionnaires can be used to collect data on nine non‐invasive variables: age; gender; BMI; waist circumference; physical activity; daily consumption of fruit and vegetables; history of antihypertensive drug treatment; history of high blood glucose; and family history of diabetes. It has been validated in many countries; for example, Sweden , the Netherlands , Greece , Spain , Hungary , Bulgaria and Slovenia . FINDRISC has shown good results, but it has often been modified because of cultural differences; for example, by adjusting the BMI and waist circumference threshold to meet Asia‐Pacific standards or by adjusting the threshold and excluding some variables from the original FINDRISC .…”
Section: Introductionmentioning
confidence: 99%
“…The cumulative diabetes incidence was more than tripled in the NDS high-risk group (NDS ≥28) at each time point (all P < 0.001, log-rank test) compared with the low-risk group (NDS <28). Among the high-risk individuals, those at higher tertiles had a steeper rise in incident diabetes compared with those at the lowest tertile (28)(29)(30). Individuals in the highest tertile of the high-risk group (NDS ≥38) had a more than sixfold (log-rank test P < 0.001) rate of incident diabetes by the 5 th year when compared with those with a baseline NDS <28.…”
Section: Resultsmentioning
confidence: 92%